Challenges of Transformative-Strategic Leadership in Developing Economies; an Analysis of Africa Leadership Approach in Economic Development - Waichungo, Peter Njuguna (International Journal of Scientific Research and Management (IJSRM), 2017)
Leadership is a process that brings about change, and not maintaining the status quo in a society. A constant change that does not coercing followers, but it is a sharing process of the same purpose and values. An important aspect of leadership is influencing others to come together around a common vision and perform a certain responsibility to bring about change toward a desirable future. Transformationalstrategic leadership is a process of complex changes in organizations that finally transforms people, and through them the whole business environment. However, though several scholars have been critical of research efforts relating to leadership in developing countries, very few have attributed Transformational-strategic leadership to change that focus on economic development in emerging economies. The need for transformativestrategic leadership and governance in developing economies is timely, important and no doubt topical, reflecting the worldwide thrust toward political and economic liberalization in the 21st century. African citizens have difficulties understanding about leadership competence, emotional and social intelligence are developed; there are challenges that definitely influence economic development. This study takes a theoretical approach and a content analysis in developing a critical role of transformational-strategic leadership in economic development laying more emphasis in African leadership challenges in the 21st century. It is an analysis of transformative- strategic leadership in developing economies and the efforts being made to address leadership challenges in Africa and the need for a locally driven strategy to develop leadership that will influence knowledge based economy. The objective of the study is to assess challenges facing leadership styles and processes that are affecting developing countries especially in Africa.